2011
DOI: 10.1111/j.1476-5381.2011.01210.x
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone inhibits Kv4.3 potassium channels by open‐channel block and acceleration of closed‐state inactivation

Abstract: BACKGROUND AND PURPOSERosiglitazone is a widely used oral hypoglycaemic agent, which improves insulin resistance in type 2 diabetes. Chronic rosiglitazone treatment is associated with a number of adverse cardiac events. The present study was designed to characterize the effects of rosiglitazone on cloned Kv4.3 potassium channels. EXPERIMENTAL APPROACHThe interaction of rosiglitazone with cloned Kv4.3 channels stably expressed in Chinese hamster ovary cells was investigated using whole-cell patch-clamp techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…Moreover, in healthy individuals, maximal plasma rosiglitazone concentrations following a single 8 mg oral dose of the drug reach approximatelỹ 370-700 ng·mL -1 (equivalent to~1-2 mM; ThompsonCulkin et al, 2002;Park et al, 2004). Thus, the majority of acute ion channel inhibitory effects seen in the two studies reported here (Jeong et al, 2011;Szentandrássy et al, 2011) occur at higher drug concentrations than are likely to occur in vivo, except -as noted by Szentandrássy et al (2011) potentially in overdose. An exception to this is inactivation state-dependent inhibition of Kv4.3 /ITO, as the Ki for this action of the drug occurs at clinically relevant concentrations (Jeong et al, 2011).…”
Section: Linked Articlesmentioning
confidence: 64%
See 4 more Smart Citations
“…Moreover, in healthy individuals, maximal plasma rosiglitazone concentrations following a single 8 mg oral dose of the drug reach approximatelỹ 370-700 ng·mL -1 (equivalent to~1-2 mM; ThompsonCulkin et al, 2002;Park et al, 2004). Thus, the majority of acute ion channel inhibitory effects seen in the two studies reported here (Jeong et al, 2011;Szentandrássy et al, 2011) occur at higher drug concentrations than are likely to occur in vivo, except -as noted by Szentandrássy et al (2011) potentially in overdose. An exception to this is inactivation state-dependent inhibition of Kv4.3 /ITO, as the Ki for this action of the drug occurs at clinically relevant concentrations (Jeong et al, 2011).…”
Section: Linked Articlesmentioning
confidence: 64%
“…The second rosiglitazone study in this issue by Jeong et al (2011) is complementary to that by Szentandrássy et al (2011), in that it provides increased insight into the likely basis of I TO inhibition by rosiglitazone. Recombinant Kv4.3 channel current was inhibited with an IC50 (half maximal inhibitory concentration) of~25 mM (Jeong et al, 2011), which is in strong agreement with the observed potency of inhibition of native ITO (Szentandrássy et al, 2011).…”
Section: Linked Articlesmentioning
confidence: 96%
See 3 more Smart Citations